Reducing R&D cycle time Robert E. Burkart presents a scheme for systematically identifying the causes of uncertainty at the "fuzzy front end" of the innovation process - Burkart, Robert E.
A diagnostic aid matches potential solutions with causes of uncertainty at the 'fuzzy front end' of the innovation process.
The systematic identification of causes of uncertainty in the R&D process and the application of appropriate solutions can shorten project cycle times and improve the efficiency and productivity of the innovation process. Individuals and teams can use a variety of TQM tools to measure and manage the upstream phase of R&D in order to deliver results faster. The matrix developed by an IRI Management Research Team is a convenient way of cross-referencing 45 of the most frequently encountered causes of uncertainty with 40 potential solutions.
Keywords: R&D Cycle Time